Pola Pembelajaran Agama Islam di Madrasah dalam Perspektif Pendidikan Holistik: Studi Kasus di Madrasah Aliyah Negeri 3 Sleman Yogyakarta - Ahmad, Zainal Arifin (Sukma: Jurnal Pendidikan, 2018)
This research aims at investigating the pattern of Islamic learning process at Yogyakarta-based Islamic senior  high  school-3 from holistic learning perspective.  The research adopts qualitative approach. The research shows  that the pattern of the  Islamic learning  process at the Islamic senior  high  school implemented  in  the  unity of  Islamic  education  curriculum with three  main inseparable  components,  i.e.  intra-curricular,  extracurricular  and hidden-curricular,  has accommodated holistic  learning  principles. The accommodation can be evaluated from the implementation of basic holistic learning principles comprising of interconnectedness, wholeness and being.  In spite of this accommodation, the research has found some weaknesses in the Islamic learning processs. First, the  development  of  the five-level of  learners  potencies   as envisioned in  holistic learning, i.e.  personal, community, social, planetary and cosmic, has  not been formulated  explicitly  in  the  curriculum  and lesson  plan.  The  existing  formulation  only  respects to  the development  of  six  dimensions  of  learners  potencies,  i.e. physical, emotional, intellectual, social, aesthetic,  and spiritual. Second, the intra-curricular learning process is  still more oriented to teaching  for  the  test and less oriented to teaching  for the whole task. Third, the subject matter of Islamic learning curriculum,  i.e. al-Qur’an-Hadis,  Akidah-Akhlak, and Fikih have not been integrated as a single unit.  The three subject  matters still  stand on their own  theme, and have not been integrated as a single unit.  The research  has successfully mapped out  the  characterizing  pattern  of  quality development  of Islamic  learning process  seen from  the perspective of holistic learning at the madrasah.[Penelitian ini bertujuan untuk mengungkapkan pola pembelajaran agama Islam di MAN 3 Sleman Yogyakarta ditinjau dari perspektif pembelajaran holistik. Penelitian ini menggunakan pendekatan kualitatif. Hasil  penelitian menunjukkan bahwa  proses pembelajaran agama Islam  di MAN 3 Sleman Yogyakarta yang diimplementasikan dalam  kesatuan program pembelajaran intrakurikuler,  ekstrakurikuler,  dan hidden curricular  secara umum telah mengarah kepada pola pembelajaran holistik. Dikatakan demikian karena dalam penerapan kesatuan tiga program pembelajaran tersebut ditemukan adanya penerapan tiga prinsip dasar pembelajaran holistik yang  meliputi connectedness, wholeness, dan  being.  Hanya saja,  dalam proses pembelajaran agama  Islam  tersebut  masih terdapat beberapa kelemahan. Pertama, secara konseptual, pengembangan lima level potensi peserta didik (personal, komunitas, sosial, planetari, dan kosmis) sebagaimana dicanangkan dalam pembelajaran  holistik  belum  terumuskan  secara  eksplisit dalam kurikulum maupun dalam perencanaan pembelajaran agama Islam. Rumusan yang ada hanya berkenaan dengan pengembangan enam dimensi potensi  peserta  didik  (fisik,  emosi,  intelektual,  sosial, estetika, dan spiritual). Kedua,  proses pembelajaran agama Islam intrakurikuler masih lebih dominan berorientasi pada teaching for the test dan kurang berorientasi pada teaching for the whole task. Ketiga, materi pelajaran agama Islam intrakurikuler  yang meliputi Akidah-Akhlak, al-Qur’an-Hadis, dan Fikih masih merupakan materi  pelajaran yang berdiri sendiri-sendiri dan belum terintegrasi sebagai satu kesatuan untuk dapat memberikan kemampuan kepada peserta didik dalam melakukan tugas-tugas yang bersifat kompleks dan menyeluruh (whole task). Penelitian ini memberi kontribusi dalam  memetakan karakteristik  pola  proses pembelajaran agama Islam di madrasah ditinjau dari perspektif  pembelajaran holistik.]